1995
DOI: 10.1007/bf00217625
|View full text |Cite
|
Sign up to set email alerts
|

Possible etiologic agents for toxic oil syndrome: Fatty acid esters of 3-(N-phenylamino)-1,2-propanediol

Abstract: The etiologic agent(s) that was responsible for the 1981 toxic oil syndrome [TOS] epidemic in Spain has not been identified. Liquid chromatography combined with atmospheric pressure ionization tandem mass spectrometry was used for the analysis of oils associated with TOS. Analyses focused on measuring 3-(N-phenylamino)-1,2-propanediol [PAP], the 3-oleyl ester of PAP [MEPAP], and the 1,2-di-oleyl ester of PAP [DEPAP]. DEPAP and MEPAP were found more frequently and at higher concentrations in TOS case-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…Therefore, in statistical terms, the association was stronger for OO PAP than for OA (28). OO PAP was also found in a sample of oil retrieved from the ITH refinery, but not in an oil derived from aniline-denatured rapeseed oil illegally produced at other refineries nor in unrefined anilinedenatured samples of rapeseed oil sent to ITH (26). Something unique must have occurred to a subset of aniline-denatured oils at ITH that both rendered them toxic and led to the appearance of OO PAP; these two consequences are not necessarily interrelated.…”
Section: Searching For the Causal Agent: Characterizing Case-related mentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, in statistical terms, the association was stronger for OO PAP than for OA (28). OO PAP was also found in a sample of oil retrieved from the ITH refinery, but not in an oil derived from aniline-denatured rapeseed oil illegally produced at other refineries nor in unrefined anilinedenatured samples of rapeseed oil sent to ITH (26). Something unique must have occurred to a subset of aniline-denatured oils at ITH that both rendered them toxic and led to the appearance of OO PAP; these two consequences are not necessarily interrelated.…”
Section: Searching For the Causal Agent: Characterizing Case-related mentioning
confidence: 91%
“…In 1995, PAP esters were found in two samples of rapeseed oil after, but not before, bringing them to a temperature of 300°C for 4 hr (26). Subsequent experiments at the Instituto de la Grasa in Seville (29,30) expanded these findings: Heating at 300°C but not at 250°C led to the formation of PAP esters.…”
Section: Finding Out the Dynamics Of The "Accident"mentioning
confidence: 96%
See 2 more Smart Citations
“…Analysis of TOS case-related oils has shown that a number of contaminants were formed through the reaction between components of the oil and the aniline denaturant (Hill et al, 1995;Bernert et al, 1987). The BIOMEDICAL CHROMATOGRAPHY Biomed.…”
Section: Introductionmentioning
confidence: 99%